Effects of Exogenous Auditory Attention on Temporal and Spectral Resolution - Günel, Basak; Thiel, Christiane M.; Hildebrandt, K. Jannis (Frontiers in Psychology, 2018)
Previous research in the visual domain suggests that exogenous attention in form of peripheral cueing increases spatial but lowers temporal resolution. It is unclear whether this effect transfers to other sensory modalities. Here, we tested the effects of exogenous attention on temporal and spectral resolution in the auditory domain. Eighteen young, normal-hearing adults were tested in both gap and frequency change detection tasks with exogenous cuing. Benefits of valid cuing were only present in the gap detection task while costs of invalid cuing were observed in both tasks. Our results suggest that exogenous attention in the auditory system improves temporal resolution without compromising spectral resolution.